ANALISIS MESIN SEPEDA MOTOR 4 LANGKAH ELECTRONIC FUEL INJECTION DENGAN MENGGUNAKAN PIGGYBACK - Muhammad Reza Habibi; Margono Sugeng (Bina Teknika, 2019)
The need for motorized vehicles at this time is very high. It can be seen from the increasing number of motorized vehicles that have sprung up with various variations and innovations. Motorized vehicles are needed as a means of transportation to support day-to-day activities both to workplaces, schools, sending goods and so on because they are faster and more efficient and fuel efficient. However, the performance capability of motorized vehicles will experience a decline from all aspects, especially the performance of the engine, due to the use or behavior of our use of the motorbike. One way to restore even improve the performance of the motorbike by giving a device to the control unit system in the form of Piggyback, so that the performance of the motorbike will return like the new one and even increase. To be able to find out the performance of the engine before and after using Piggyback, a motor test was performed on the engine by dynotest on the dynamometer. So this reason the author can analyze how much changes in power, torque and fuel to air ratio occur.